2017
DOI: 10.1002/aur.1807
|View full text |Cite
|
Sign up to set email alerts
|

White matter compromise in autism? Differentiating motion confounds from true differences in diffusion tensor imaging

Abstract: Scientific abstract Background Common findings from diffusion tensor imaging (DTI) in autism spectrum disorder (ASD) include reduced fractional anisotropy (FA), and increased mean and radial diffusivity (MD, RD) of white matter tracts. However, findings may be confounded by head motion. We examined how group-level motion matching affects DTI comparisons between ASD and typically developing (TD) groups. Methods We included 57 ASD and 50 TD participants, comparing 3 subsets at increasing levels of motion-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 79 publications
(98 reference statements)
1
14
0
Order By: Relevance
“…Across both time samples, the ASD group did not exhibit significant differences in the connectome compared with TDC, which is inconsistent with the earlier findings of diffuse white matter disruption 29 . Given the careful quality control for DSI data and tight motion-matching in the current data, as well as comparable sample sizes and high-functioning cohorts with earlier studies 29 , this finding might suggest that motion confounds have inflated previously reported white matter differences in ASD at the group level 30 . The present null finding in a diagnostic effect may also highlight the advantage of performing a longitudinal analysis to capture variance across the diagnostic groups with regards to differences in their developmental trajectories.…”
Section: Discussionmentioning
confidence: 53%
“…Across both time samples, the ASD group did not exhibit significant differences in the connectome compared with TDC, which is inconsistent with the earlier findings of diffuse white matter disruption 29 . Given the careful quality control for DSI data and tight motion-matching in the current data, as well as comparable sample sizes and high-functioning cohorts with earlier studies 29 , this finding might suggest that motion confounds have inflated previously reported white matter differences in ASD at the group level 30 . The present null finding in a diagnostic effect may also highlight the advantage of performing a longitudinal analysis to capture variance across the diagnostic groups with regards to differences in their developmental trajectories.…”
Section: Discussionmentioning
confidence: 53%
“…First, although a wealth of functional, EEG, and DTI data suggest disrupted connectivity in ASD [20, 69], the validity of these findings is sometimes questioned. Head motion artifact in particular has been proposed as the cause of group difference in ASD versus typically developing control DTI studies [7073], as FA is known to substantial decrease with DWI slice-level motion artifact [74]. Here, we present longitudinal imaging data acquired in infants at high risk of ASD with a common genetic diagnosis over the period of early brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Image artifacts associated with head motion are a significant confound in ASD research. Head motion has shown to be increased in ASD [72] and to significantly impact DWI results [73]. Accordingly, in addition to utilizing a noctoral sleep protocol [47] and state of the art within volume motion correction [68], we quantified head motion using the root-mean-square (RMS) displacement of both the mean absolute intervolume displacement with respect to the first image of each acquisition and the mean relative intervolume displacement between each preceding image in the sequence.…”
Section: Methodsmentioning
confidence: 99%